Academic Senate Minutes 2011-12-01 - Academic Senate:::::::::
Revision to the Priority Registration Policy – Approved. Special Report: The Green Music Center and SSU's Academic Mission. Resolution Regarding Suspension of CSU Online Initiative – Approved.Resolution Regarding Protest at the University – First Reading.